Full-length chloroplast genome of Dongxiang wild rice reveals small single-copy region switching - Liang, Jianguang; Chen, Rui; Zhang, Fantao; Wang, Qian; Yang, Yingxia; Lv, Mingjie; Yan, Shuangyong; Gao, Shan (Frontiers in Plant Science, 2022)
Background Plant chloroplast DNA (cpDNA) typically has a circular structure, including a large single-copy region (LSC), a small single-copy region (SSC) and two inverted repeats (IR1 and IR2). The organization of these four elementary regions LSC-IR1-SSC-IR2 is highly conserved across all plant cpDNAs. Very few structural variations (SVs) occurring at the elementary-region level have been reported. Results In the present study, we assembled the full-length cpDNA of Dongxiang wild rice line 159 (DXWR159). Using the long PacBio subreads, we discovered a large inversion of SSC and a large duplication of IR in DXWR159 cpDNAs. Significantly, we reported for the first time forward and reverse SSCs of cpDNAs in similar proportions and named the frequent inversion of a whole SSC as SSC switching. Conclusions Our study helps researchers to correctly assemble the chloroplast genomes. Our recombination model explained the formation of large SVs in cpDNAs and provided insights into a novel scientific question that if there are common mechanisms in the formation or translocation of all kinds of transposon-like elements (TLEs). We propose that: (1) large inversion is the most accepted mutation type of SVs in cpDNAs; (2) SSC switching ubiquitous occurs in plant cpDNAs; and (3) further investigation of molecular mechanism underlying SSC switching may reveal new driving forces for large SVs.